Performance Model of Courier Service in Pademangan, North Jakarta: Discipline, Incentives, and Competence - Suryana, Lilis (Dinasti Publisher, 2024)
This study aims to analyze the performance of couriers in the expedition industry in the Pademangan area of North Jakarta. The research sample does not include the entire population but only a subset. The sampling method follows the theory of Hair, which provides guidelines for determining sample size in structural equation modeling (SEM). Data for this research were collected directly through a questionnaire, which is a measurement tool containing a series of written questions or statements given to respondents to gather responses relevant to the research needs. Primary data were obtained from the distribution of the questionnaire, with research variables including Performance, Management Information Systems, Training, and Organizational Culture. The data were analyzed using Partial Least Squares (PLS) methodology. Work discipline significantly affects courier performance, while incentives and competence do not have a significant impact. The three independent variables together explain 80.9% of the variation in courier performance. The company needs to reassess its incentive programs and competency development to enhance their effectiveness and consider further research to identify additional factors influencing courier performance.